2010
DOI: 10.1083/jcb.201002041
|View full text |Cite
|
Sign up to set email alerts
|

LIM kinases are required for invasive path generation by tumor and tumor-associated stromal cells

Abstract: Leading cells require LIMK for matrix degradation and invadopodia formation during collective cell migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
149
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(169 citation statements)
references
References 59 publications
14
149
2
4
Order By: Relevance
“…1) (5). Results from clinical and basic studies indicate that LIM kinases are important factors in cancer cell invasion and metastasis (5,12), while in vivo studies indicated that interfering with LIMK function inhibited metastasis (13,14). These reports are consistent with the hypothesis that LIMK inhibition would effectively reduce cancer cell invasion and metastasis.…”
Section: Limksupporting
confidence: 79%
See 1 more Smart Citation
“…1) (5). Results from clinical and basic studies indicate that LIM kinases are important factors in cancer cell invasion and metastasis (5,12), while in vivo studies indicated that interfering with LIMK function inhibited metastasis (13,14). These reports are consistent with the hypothesis that LIMK inhibition would effectively reduce cancer cell invasion and metastasis.…”
Section: Limksupporting
confidence: 79%
“…Although the use of LIMK inhibitors to block cancer cell invasiveness and metastasis was one initial potential application (12), several recent reports indicate that they may be useful for treating primary tumors (21,25). In addition, the observation that LIMK inhibition sensitizes tumor cells to genotoxic chemotherapeutic agents (15) suggests that LIMK inhibitors might be effective in combination therapies.…”
Section: Future Directionsmentioning
confidence: 99%
“…6 Using threedimensional invasion assays we found that LIMK inhibition by either method resulted in significantly decreased invasion. 7 Interestingly, although many reports in the literature have implicated a specific role for either LIMK1 or LIMK2 in various processes, [8][9][10][11] we found that the selective knockdown of either protein alone had only small effects that were additive when both were targeted or inhibited simultaneously. Similar results were reported for individual versus combined knockdown of LIMK1 and LIMK2 in a zebrafish xenograft model of pancreatic cancer metastasis.…”
mentioning
confidence: 77%
“…23 Given that inhibiting LIMK also reduced matrix degradation, we also wondered whether proteolysis actually facilitated contraction. When MT1-MMP, which is the major matrix metalloprotease in CAFs, 7 was knocked down there was a significant inhibition in collagen contraction. Therefore, we concluded one way LIMK activity contributes to matrix remodeling is to facilitate the proteolysis of cross-linked matrix proteins that would otherwise be too rigid for contraction to occur.…”
mentioning
confidence: 99%
“…LIM kinases are therefore centrally positioned regulators of actin cytoskeletal dynamics and also play important roles in microtubule organization. 2,3 LIMK1 has been reported to play a key regulatory role in tumour cell invasion and the level of LIMK1 is increased in invasive breast, 4 prostate, 5 and pancreatic 6 cancer cell lines in comparison with less invasive cells. Overexpression of LIMK1 in MCF-7 and in MDA MB-231 human breast cancer cell lines increased their motility, while inhibition of LIMK1 activity in MDA MB-231 cells by expression of a dominant negative LIMK1 resulted in decreased motility and formation of osteolytic bone lesions in an animal model of tumour invasion.…”
mentioning
confidence: 99%